The Dichotomy of Hypocrisy and Sacrifice in Modern Society: An Analysis of “The Kite Runner” by Khaled Hosseini - Anisa Shahzadi; Nazia Anwar; Ayesha Zuree (Journal of Peace, Development and Communication, 2024)
This study presents a nuanced critical analysis of Khaled Hosseini’s acclaimed novel “The Kite Runner” (2003), delving into the major themes of hypocrisy and sacrifice, as well as guilt and redemption. Through a rigorous analytical approach, this research undertakes a comprehensive examination of the intricacies of these themes within the novel’s narrative framework. The protagonist, Amir, grapples with the repercussions of prioritizing convenience over morality, and his subsequent quest for redemption serves as a catalyst for exploring the transformative power of sacrifice, exemplified by Baba’s selfless relinquishment of wealth and status (Hosseini, 2003). This library-based research also illuminates the various tribulations and hardships endured by Afghan society, providing a rich contextual understanding of the cultural and historical backdrop against which the story unfolds (Ahmed-Ghosh, 2003). By scrutinizing the complex interplay between these themes, this study aims to contribute meaningfully to a deeper understanding of the novel’s thematic landscape and its implications for literary analysis.